2018
DOI: 10.1177/1091581817753607
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of the Dopaminergic System in Seizure and Oxidative Damage Induced by Tramadol

Abstract: Tramadol (TR) is a synthetic analgesic drug with central function that can induce seizures even at therapeutic doses. The exact mechanism of TR effect on seizure generation is not clear, but inhibition of the serotonin and nitric oxide pathways and inhibitory effects on GABA receptors are the most common hypotheses about the seizure-inducing mechanism of the TR. This study aimed to evaluate the role of dopaminergic system on the seizure and oxidative damage induced by TR using agonist and antagonist drugs of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The mechanism underlying the increased generation of the reactive oxygen species (ROS) via tramadol consumption can be explained by the findings of Mohamed et al (2015), who reported a significant decrease in the activities of mitochondrial electron transport chain complexes I, III, and IV complexes, but not complex II, in rats exposed to tramadol abuse. Moreover, Bameri et al (2018) explained that the dopaminergic system is also involved in tramadol-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the increased generation of the reactive oxygen species (ROS) via tramadol consumption can be explained by the findings of Mohamed et al (2015), who reported a significant decrease in the activities of mitochondrial electron transport chain complexes I, III, and IV complexes, but not complex II, in rats exposed to tramadol abuse. Moreover, Bameri et al (2018) explained that the dopaminergic system is also involved in tramadol-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that tramadol could reduce the synaptic phosphorylation state of NR2B at Tyr1472, which may be closely related to its effect on reduced spinal synaptic NR2BR expression. The analgesic mechanisms of tramadol are complicated, and in addition to the oxidative damage side effect of tramadol, which may also affect the pain perception process [ 34 , 35 ], further investigation will be required to elucidate the mechanisms in detail. The present study is the first to report that NR2BR might be a potential downstream target of tramadol.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase (CAT) is a heme-containing enzyme that catalyses the dismutation of H2O2 to molecular oxygen and water, thereby lessening the risk of hydroxyl radical formation [37]. Several studies have pointed to the relationship between the chronic opioid administration and increased production of reactive oxygen species (ROS) [38,39,40]. Oxidative stress is an imbalance between ROS production of and the ability of antioxidant defenses to neutralize them.…”
Section: Tramadol Interferes With the Free Radical Scavenging Prowess Of Catalasementioning
confidence: 99%